PENERAPAN MODEL CLIS UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD - ., Trisna Kurniasih; ., Dr. I Nyoman Jampel,M.Pd; ., Putu Nanci Riastini, S.Pd., M.Pd. (Universitas Pendidikan Ganesha, 2016)
Penelitian ini bertujuan untuk mengetahui peningkatkan hasil belajar IPA pada siswa kelas V SDN 2 Yehsumbul setelah penerapan model pembelajaran Children Learning In Science (CLIS). Penelitian ini merupakan penelitian tindakan kelas (PTK) yang dilaksanakan dalam dua siklus. Subjek penelitian adalah siswa kelas V SDN 2 Yehsumbul tahun pelajaran 2015/2016 yang berjumlah 28 orang. Objek penelitian adalah hasil belajar IPA. Pengumpulan data dalam penelitian ini dilakukan dengan metode tes. Data yang didapatkan selanjutnya dianalisis untuk memperoleh nilai rata-rata kelas dan ketuntasan belajar secara klasikal Hasil penelitian menunjukkan adanya peningkatan terhadap hasil belajar IPA siswa. Sebelum tindakan, nilai rata-rata kelas sebesar 68 dan ketuntasan belajar sebesar 32,14%. Setelah dilakukan tindakan pada siklus I, nilai rata-rata kelas mengalami peningkatan menjadi 71 dan ketuntasan belajar sebesar 57,14%. Pada siklus II, terjadi peningkatan nilai rata-rata kelas sebesar 83,21 dan ketuntasan belajar 100% Berdasarkan hasil penelitian tersebut, dapat disimpulkan bahwa penerapan model pembelajaran Children Learning In Science (CLIS) dapat meningkatkan hasil belajar IPA siswa kelas V SDN 2 Yehsumbul.Kata Kunci : Kata kunci: children learning in science (CLIS), hasil belajar IPA The aim of this study is to know the improvement of students’ science achievements of fifth grade students in SDN 2 Yeh Sumbul after applying Children Learning In Science model. This classroom action research was conducted in two cycles. The subjects were 28 fifth grade students in academic year 2015/2016. The object of this study was students’ science achievements. Multiple choices tests were conducted for collecting data. The data obtained are analyzed to obtain the value of the average grade and mastery learning classical. The results showed an increase of the IPA student learning outcomes. Before the action, the average value of 68 and a grade of 32.14% completeness study. After the action on the first cycle, the value of the average grade has increased to 71 and complete learn by 57.14%. In the second cycle, an increase in the value of the average grade of 83.21 and 100% completeness study Based on these results, it can be concluded that the application of learning models Children Learning In Science (CLIS) can improve learning outcomes fifth grade science students at SDN 2 Yehsumbul. study shows that there are significant improvements toward the students’ science achievements. Before the actions were conducted, the average percentage of students’ science achievements was 68%. It increased after conducting the first cycle becoming 71% and increased up to 82.2% in the second cycle. Based on these result, it can be concluded that the application of Children Learning In Science improved significantly the students’ science achievements of fifth grade students in SDN 2 Yeh Sumbul.keyword : Keywords: children learning in science (CLIS), students’ science achievements